Antagonistic Effects of Lipids Against the Anti-Escherichia coli and Anti-Salmonella Activity of Thymol and Thymol-β-d-Glucopyranoside in Porcine Gut and Fecal Cultures In Vitro - Anderson, Robin C.; Levent, Gizem; Petrujkić, Branko T.; Harvey, Roger B.; Hume, Michael E.; He, Haiqi; Genovese, Kenneth J.; Beier, Ross C.; Poole, Toni L.; Crippen, Tawni L.; Nisbet, David J. (Frontiers in Veterinary Science, 2021)
Strategies are sought to reduce the carriage and dissemination of zoonotic pathogens and antimicrobial resistant microbes within food-producing animals and their production environment. Thymol (an essential oil) is a potent bactericide in vitro but in vivo efficacy has been inconsistent, largely due to its lipophilicity and absorption which limits its passage and subsequent availability in the distal gastrointestinal tract. Conjugation of thymol to glucose to form thymol-β-D-glucopyranoside can decrease its absorption but in vivo passage of effective concentrations to the lower gut remains suboptimal. Considering contemporary swine diets often contain 5% or more added fat (to increase caloric density and reduce dustiness), we hypothesized that there may be sufficient residual fat in the distal intestinal tract to sequester free or conjugated thymol, thereby limiting the availability and subsequent effectiveness of this biocide. In support of this hypothesis, the anti-Salmonella Typhimurium effects of 6 mM free or conjugated thymol, expressed as log10-fold reductions of colony forming units (CFU) mL-1, were diminished 90 and 58%, respectively, following 24-h in vitro anaerobic fecal incubation (at 39oC) with 3% added vegetable oil compared to reductions achieved during culture without added oil (6.1 log10 CFU/mL). The antagonistic effect of vegetable oil on the bactericidal effect of free and conjugated thymol against Escherichia coli K88 tested similarly were diminished 86 and 84%, respectively, compared to reductions achieved in cultures incubated without added vegetable oil (5.7 log10 CFU/mL). Inclusion of taurine (8 mg/mL), bile acids (0.6 mg/mL) or emulsifiers such as polyoxyethylene-40 stearate (0.2%), Tween 20 or Tween 80 (each at 1%) in the in vitro incubations had little effect on vegetable oil-caused inhibition of free or conjugated thymol. Based on these results, it seems reasonable to suspect undigested lipid in the distal gut may limit the effectiveness of free or conjugated thymol. Accordingly, additional research is warranted to learn how to overcome obstacles diminishing bactericidal activity of free and conjugated thymol in the lower gastrointestinal tract of food-producing animals.